From Fur to Felt Hats: The Hudson’s Bay Company and the Consumer Revolution in Britain, 1670-1730 - Hawkins, Natalie (Université d'Ottawa / University of Ottawa, 2014)
This dissertation seeks to explore the wide reaching effects of the ‘Consumer Revolution of the Augustan Period’ (1680-1750) by examining the Hudson’s Bay Company from the perspective of the London metropole. During this period, newly imported and manufactured goods began flooding English markets. For the first time, members of the middling and lower sorts were able to afford those items which had previously been deemed ‘luxuries.’ One of these luxuries was the beaver felt hat, which had previously been restricted to the wealthy aristocracy and gentry because of its great cost. However, because of the HBC’s exports of beaver fur from Rupert’s Land making beaver widely available and therefore, less expensive, those outside of the privileged upper sorts were finally able to enjoy this commodity. Thus, the focus here will be on the furs leaving North America, specifically Hudson’s Bay, between 1670 and 1730, and consider the subsequent consumption of those furs by the British and European markets. This thesis examines English fashion, social, economic, and political history to understand the Hudson’s Bay Company and the Consumer Revolution, and their effects on one another.
Keywords: Hudson's Bay Company; Consumer Revolution; Eighteenth Century; Beaver Hat; London; fashion; Beaver; Hudson's Bay; Rupert's Land; fur trade; Britain